If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1(2n + -9) = 3 + -3n Reorder the terms: 7 + -1(-9 + 2n) = 3 + -3n 7 + (-9 * -1 + 2n * -1) = 3 + -3n 7 + (9 + -2n) = 3 + -3n Combine like terms: 7 + 9 = 16 16 + -2n = 3 + -3n Solving 16 + -2n = 3 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 16 + -2n + 3n = 3 + -3n + 3n Combine like terms: -2n + 3n = 1n 16 + 1n = 3 + -3n + 3n Combine like terms: -3n + 3n = 0 16 + 1n = 3 + 0 16 + 1n = 3 Add '-16' to each side of the equation. 16 + -16 + 1n = 3 + -16 Combine like terms: 16 + -16 = 0 0 + 1n = 3 + -16 1n = 3 + -16 Combine like terms: 3 + -16 = -13 1n = -13 Divide each side by '1'. n = -13 Simplifying n = -13
| -3.2x+14.08=-4.8 | | 3x+4-5x=10x+5 | | y^3+8y^2-23y-210=0 | | -3/10=x-5/8 | | 125=-5(3+x) | | 2x+3=5x-3 | | S=4k+4w | | -3(x-2)=16 | | t^2-2t-120=0 | | 3x+x=130 | | 3(n+5)+2=60 | | 4w-6= | | .20*40= | | n^2=6n+72 | | b/4+5=14 | | x+y=130 | | a/9=6 | | -7=11+x | | 2x-5x=-6 | | 3*76= | | (9x-81)=12 | | 34/6=2x+1/3 | | 3x^2-2x-12x+8= | | 3x+y=130 | | 6y=30y+140 | | 2abc+d=3 | | -5y-2y+3y=9 | | -19-(-4)=x | | -10-(-5)=x | | -18=6x-4x | | 3/4=z/16 | | 2a+-5b+5a+-1b= |